Techniques in epilepsy surgery the MNI approach - Olivier, André 1938- (Cambridge University Press, 2012)
Techniques in Epilepsy Surgery presents the operative procedures used in the treatment of intractable epilepsy in a practical, clinically relevant manner. Founded by pioneering neurosurgeon Wilder Penfield, the Montreal Neurological Institute (MNI) is a leading global centre of epilepsy surgery and this volume reflects the Institute's approach, combining traditional techniques with modern neuronavigation-based approaches. There is an emphasis on mastering the important trilogy of topographic, vascular and functional anatomy of the brain. The basic anatomical and physiological mechanisms underlying epilepsy are presented in a practical manner, along with the clinical seizure evaluation that leads to a surgical hypothesis. The consultation skills and investigations necessary for appropriate patient selection are discussed, as well as pitfalls and the avoidance of complications. This is an invaluable resource not only for neurosurgeons, neurosurgical residents and fellows in epilepsy surgery, but also for neurologists, and others who provide medical care for patients with intractable epilepsy